Preparation method and application of flexible resistance-type humidity sensor based on Zn / Ag / PEO nanowire stacking
The preparation of flexible resistive humidity sensors through Zn/Ag/PEO nanowire stacking and electrospinning direct writing technology has solved the problems of complex processes and high costs in the existing technology, and realized a flexible and low-cost humidity sensor, suitable for diversification Application scenarios and improve response range and speed.
Patent Information
- Application Number
- CN202411389907.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
The existing flexible humidity sensor preparation process is complex, has high cost, and has a narrow response range and slow speed, making it difficult to be suitable for diverse application scenarios.
The flexible resistive humidity sensor was prepared by electrospinning direct writing technology using Zn/Ag/PEO nanowire stacking, and the solution of silver acetate, zinc acetate and polyethylene oxide in anhydrous ethanol and isopropanolamine was used to form a particle-free ink. Interfinger electrode and nanowire structures are formed by screen printing and high temperature sintering.
It realizes a flexible resistive humidity sensor with low cost and simple process, with a wide range of application adaptability and high environmental tolerance, a wide response range and fast speed, and is suitable for food safety and industrial inspection and other fields.
Smart Images

Figure CN119246628A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible electronic devices, and in particular relates to a preparation method and application of a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking. Background Art
[0002] Humidity, as one of the important environmental parameters, has important applications in fields such as intelligent monitoring. Therefore, humidity sensors used to monitor humidity have become a widely used sensor. Existing humidity sensors can be divided into many types, including resistive, capacitive, impedance, quartz crystal microbalance (QCM), surface acoustic wave (SAW), field effect transistor (FET) and optical fiber humidity sensors. At present, most commercial traditional humidity sensors are rigid, mechanically brittle, and cannot sustain large deformations and instantaneous impacts. The sensors made from them are inflexible and easily damaged, and are difficult to apply to application scenarios such as humidity detection on curved surfaces. In contrast, the flexibility of flexible humidity sensors is suitable for various surfaces to expand their application areas, including but not limited to health monitoring, food safety monitoring, industrial testing, air quality monitoring and non-contact human-computer interaction.
[0003] The selection of sensitive materials for the humidity sensitive layer and the preparation method of the sensing layer are crucial. At present, the most commonly used commercial resistive flexible humidity sensors have high production costs and complex preparation processes. The sensitive materials are mostly liquid, and the humidity sensitive layer is mostly applied by drop coating or spin coating, which is not conducive to industrial production and application. Recently, one-dimensional nanofibers have also been developed for the preparation of sensitive materials for humidity sensors due to their high specific surface area and the advantages of easy formation of pore structures to increase active sites for water molecule binding. However, some existing humidity sensors based on one-dimensional nanofibers still have the defects of too narrow linear response range, slow response speed, and greater environmental influence.
[0004] Therefore, it is of far-reaching significance to prepare a flexible resistive humidity sensor with low cost, simple process and good humidity-sensitive performance to meet the needs of flexible humidity sensors to adapt to diversified actual production applications. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a preparation method and application of a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking.
[0006] The specific technical solution adopted by the present invention is:
[0007] A method for preparing a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking comprises the following steps:
[0008] (1) dissolving silver acetate and zinc acetate in deionized water, and after complete dissolution, adding anhydrous ethanol, isopropanolamine, and PEO in sequence, sealing the solution, and stirring and mixing to obtain a particle-free ink;
[0009] (2) removing pollutants from the surface of the flexible substrate, and forming electrodes on the top surface of the flexible substrate by screen printing a particle-free ink;
[0010] (3) depositing precursor fibers on the top surface of the electrode by electrospinning direct writing technology, wherein the precursor fibers are Zn / Ag / PEO precursor fibers;
[0011] (4) After the precursor fiber is deposited, it is placed on a high-temperature sintering table for sintering to form Zn / Ag / PEO nanowires, and then naturally cooled to room temperature;
[0012] (5) After cooling to room temperature, the electrodes are led out through the wires to obtain a flexible resistive humidity sensor.
[0013] Furthermore, the electrodes are interdigitated electrodes.
[0014] Furthermore, the precursor fiber is obtained by direct writing and depositing multiple layers back and forth in a direction perpendicular to the interdigital direction of the electrode through the electrospinning direct writing technology.
[0015] Furthermore, the precursor fiber is obtained by direct writing and depositing 100 layers back and forth in a direction perpendicular to the interdigital direction of the electrode through electrospinning direct writing technology.
[0016] Furthermore, the electrode raw materials include but are not limited to single or multiple metals of Ag, Cu, Ni and Au;
[0017] Furthermore, the electrode is designed to have 20 pairs of 40 fingers, each finger has a size of 100 μm×100 μm, and the gap between the fingers is 100 μm.
[0018] Furthermore, the particle-free ink has a silver acetate content of 1.4%, a zinc acetate content of 3.5%, a PEO content of 14%, a water-to-anhydrous ethanol volume ratio of 1:2, and a silver-to-zinc ratio of 1:2;
[0019] Furthermore, the flexible substrate used is polyimide with a thickness of 1 mm;
[0020] Furthermore, the electrospinning direct writing technology is to store the ink in a syringe and deliver it to the needle through a precision injection pump, and the flexible substrate is driven by a motion platform to deposit nanofibers according to a pre-designed trajectory;
[0021] Furthermore, the Zn / Ag / PEO nanowires are formed after sintering at 50° C. for 60 minutes on a high-temperature sintering table; the Zn / Ag / PEO nanowires have a one-dimensional porous bionic nanostructure.
[0022] Correspondingly, the present invention also provides a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking, which is prepared by the above-mentioned preparation method, and the flexible resistive humidity sensor includes a flexible substrate, an electrode and a humidity sensitive material layer; the electrode is arranged on the top surface of the flexible substrate, the humidity sensitive material layer is arranged on the top surface of the electrode, and the electrode is led out by a wire; the humidity sensitive material layer is Zn / Ag / PEO nanowire.
[0023] The present invention also provides an application of the above-mentioned flexible resistive humidity sensor, and applies the flexible resistive humidity sensor in the field of detection, and the detection field includes but is not limited to food safety detection and industrial detection.
[0024] Furthermore, the flexible resistive humidity sensor operates in a relative humidity range of 11% to 85% RH.
[0025] Furthermore, the flexible resistive humidity sensor operates in a temperature range of 0°C to 120°C.
[0026] The beneficial effects of the present invention are:
[0027] 1) The flexible resistive humidity sensor design of the present invention is lower in cost and more conducive to large-scale production compared to other flexible resistive humidity sensors;
[0028] 2) The flexible resistive humidity sensor of the present invention is simpler in structure than the traditional multi-touch sensor, has fewer process steps, and is easier to manufacture;
[0029] 3) The base material used in the present invention has good softness, and the resistance change rate is maintained at about 3.97% under repeated bending changes of 0-90°, indicating that the functional material layer is little affected by bending deformation and can be widely used in more fields such as biomedicine and wearable devices.
[0030] 4) The flexible resistive humidity sensor of the present invention is flexible and scalable. A variety of response performances can be designed to meet the needs of different scenarios by simply changing the number of fiber stacking layers and the sintering time. It can be used in fields including food safety testing and industrial testing. Its shape can be designed according to functional requirements and has broad application prospects.
[0031] 5) The humidity sensitive material layer of the present invention has a unique fiber structure that makes the sensor highly environmentally tolerant and will not be damaged in harsh environments such as high temperature and high humidity. Compared with other flexible resistive humidity sensors, the flexible resistive humidity sensor of the present invention has a wider linear humidity response range of 11.30%RH-81.70%RH, a higher sensitivity of 3kΩ / 1%RH, a humidity hysteresis of 2%RH and a fast response time of 1.7s. The average resistance change rate is 2.8% in a high humidity environment (81.70%RH), 2.4% in a low humidity environment (11.30%RH), less than 1.2% in a high temperature environment (100°C), and less than 0.4% in a low temperature environment (0°C), indicating that it has both low environmental temperature dependence and good long-term stability, and can continuously and stably monitor humidity characteristics in complex environments.
[0032] 6) The present invention adopts electrospinning direct writing technology to synthesize one-dimensional nanofibers of humidity sensitive material layer, which has the advantages of small scale, high precision, low cost-effectiveness, and high substrate versatility. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the electrospinning direct writing equipment and process;
[0034] Figure 2 Schematic diagram of the preparation of particle-free metal complex ink;
[0035] Figure 3 This is a schematic diagram of the structural decomposition of the flexible resistive humidity sensor;
[0036] Figure 4 Schematic diagram of high performance fiber formation;
[0037] Figure 5 This is the response mechanism diagram of the humidity sensor;
[0038] Figure 6 It is a dot-line graph of the responsivity of the flexible resistive humidity sensor at 11-95%RH;
[0039] Figure 7 It is a hysteresis curve diagram of the flexible resistive humidity sensor;
[0040] Figure 8 It is a humidity dynamic response curve diagram of the flexible resistive humidity sensor;
[0041] Fig. 9 A food environment detection system built for flexible humidity sensors. DETAILED DESCRIPTION
[0042] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.
[0043] Example 1
[0044] A method for preparing a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking comprises the following steps:
[0045] (1) Take the particle-free ink with 1.4% silver acetate content, 3.5% zinc acetate content, 14% PEO content, water and anhydrous ethanol volume ratio of 1:2, and silver-zinc ratio of 1:2 as an example. First, 0.07g silver acetate and 0.18g zinc acetate are dissolved in 1.53g deionized water. After complete dissolution, 2.23g ethanol, 0.40g isopropanolamine, and finally 0.7g PEO are added. After sealing, magnetic particles are placed and stirred at 25°C for 72 hours.
[0046] (2) Using PI with a thickness of 1 mm as the substrate, a needle with an outer diameter of 0.23 mm and an inner diameter of 0.08 mm was connected to the positive electrode of a high-voltage power supply (DW-SA403-1ACE5, Tianjin Dongwen High Voltage Power Supply Co., Ltd., China). The electrode was prepared by screen printing. The pattern design of the interdigitated electrode was completed using AutoCAD software. The interdigitated electrode here was designed to have 20 pairs of 40 fingers, each interdigitated electrode was 100 μm × 100 μm in size, and the interdigital gap was 100 μm. The PI film was spread flat on the screen printing table, and the silver interdigitated electrodes were printed using conductive silver glue under the interdigitated mask, and the electrodes were dried on a heating table.
[0047] (3) Driven by a motion platform (POT-G-MOT-F09-06, Jiangxi Liansheng Precision Optical Platform), it is used to deposit multiple layers of Zn / Ag / PEO conductive fibers with a certain structural morphology on the film according to a pre-designed trajectory perpendicular to the direction of the interdigital electrodes. Specifically, the electrodes are placed flat on the motion platform, and a certain amount of solution is extracted by a precision syringe pump (Pump 11Pico Plus Elite, Harvard Apparatus, USA) for spinning direct writing. The pre-designed driving code is used to write back and forth in the direction perpendicular to the interdigital direction to deposit 100 layers of fibers, and then placed on a high-temperature sintering table for sintering at 50°C for 60 minutes and cooled to room temperature;
[0048] (4) Finally, the electrode wires are led out through conductive silver glue and the wires are connected with copper foil to obtain a resistive flexible humidity sensor.
[0049] The effect of the present invention is further described below in conjunction with the comprehensive performance measurement results:
[0050] Figure 1 Schematic diagram of electrospinning direct writing equipment and process.
[0051] Figure 2 Schematic diagram of the preparation of particle-free metal complex ink.
[0052] Figure 3 This is a schematic diagram of the humidity sensor structure. A flexible resistive humidity sensor includes a flexible substrate, an electrode and a humidity sensitive material layer; the electrode is arranged on one surface of the flexible substrate, the humidity sensitive material layer is arranged on the other surface of the electrode, and the flexible substrate and the humidity sensitive material layer are separated by the electrode; the electrode is led out by a wire.
[0053] Figure 4 In order to design the structural characteristics of the humidity sensitive material of the humidity sensor, based on the principle that sponges in nature store and absorb a large amount of water molecules through their unique pore structure, we designed a Zn / Ag / PEO conductive fiber with a sponge-like pore structure by low-temperature sintering post-treatment. Compared with Ag / PEO conductive fibers prepared by silver-based ink, Zn / Ag / PEO conductive fibers with a sponge-like pore structure have a faster sintering speed and less temperature dependence.
[0054] Figure 5 The working principle of the flexible resistive humidity sensor with the above structure is shown as follows: When the humidity sensitive material absorbs water vapor from the external environment, its conductive fibers adsorb water molecules. In relatively low humidity, water molecules cover the active sites of the conductive fibers due to electrosorption, fill the pores, increase the contact area between the nanoparticles, and form a unidirectional conductive path on the interdigitated electrodes. As the humidity increases, the number of water molecules physically adsorbed on the surface of the functional material increases, forming a water layer. The H3O generated by the dissociation of water molecules + Cross-conductive channels are formed between the fibers. When the relative humidity is high, a continuous water film is formed between the fibers. The main mechanism of humidity sensing can be explained by the Grotthuss mechanism. Proton hopping occurs between adjacent water molecules, which improves the conductivity of the sensor. Different humidity conditions form different numbers of conductive paths between the interdigitated electrodes, resulting in corresponding changes in the edge resistance, which can measure the humidity of the environment.
[0055] Figure 6 The humidity response curve of ZAHS is shown in Figure 2. The response gradually increases with the increase of ambient humidity. When the relative humidity is between 11% and 81%, the ZAHS response has a good linear relationship with humidity, and the humidity response range is large.
[0056] Figure 7The humidity hysteresis curve of ZAHS shows that when the humidity gradually increases from 11.3%RH to 94.6%RH, the resistance of the sensor decreases with the increase of humidity. The hysteresis can be expressed by the maximum horizontal coordinate difference between the adsorption curve and the desorption curve in the same horizontal direction. At 21%RH and 56%RH, the hysteresis is 1.07% and 1.31% respectively, indicating that ZAHS has good desorption reversibility.
[0057] Figure 8 The dynamic response recovery curve of ZAHS under different relative humidity. When the resistance value of 11.3%RH is used as the baseline, the humidity sensor shows different resistances when ZAHS is placed at different relative humidity levels from 23.1% to 94.6%RH at 25°C. As the relative humidity of the sensor gradually increases, the sensor resistance decreases accordingly. The difference in resistance change at 11.3-81.7%RH is large, indicating that its sensing range is 11–95%RH, the effective sensing range is 11.3-81.7%RH, the humidity response range is large, and it has good response performance in both high and low humidity environments.
[0058] Fig. 9 This is a test of the sensor's application in food testing. Ambient humidity is an important factor affecting the quality of food storage. Too high humidity can cause food to get damp, which in turn causes food to spoil; too low humidity can cause food to be too dry, affecting the taste and quality of food. Grain storage occupies a large area horizontally and has a high ceiling vertically. The humidity conditions in all directions are difficult to control accurately, and some grains often get damp and spoil. Sensors used to monitor humidity need to have low economic cost and low environmental dependence. The sensor has excellent humidity sensitivity, low manufacturing cost and good environmental compatibility. It can be used to respond to large-scale grain surface humidity in real time and monitor grain moisture.
[0059] Although the above embodiments have been described, once those skilled in the art know the basic creative concepts, they can make additional changes and modifications to these embodiments. Therefore, the above description is only an embodiment of the present invention and does not limit the patent protection scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the specification and drawings of the present invention, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stacking, characterized in that: The steps include: (1) dissolving silver acetate and zinc acetate in deionized water, and after complete dissolution, adding anhydrous ethanol, isopropanolamine, and PEO in sequence, sealing the solution, and stirring and mixing to obtain a particle-free ink; (2) removing pollutants from the surface of the flexible substrate, and forming electrodes on the top surface of the flexible substrate by screen printing a particle-free ink; (3) depositing precursor fibers on the top surface of the electrode by electrospinning direct writing technology, wherein the precursor fibers are Zn / Ag / PEO precursor fibers; (4) After the precursor fiber is deposited, it is placed on a high-temperature sintering table for sintering to form Zn / Ag / PEO nanowires, and then naturally cooled to room temperature; (5) After cooling to room temperature, the electrodes are led out through the wires to obtain a flexible resistive humidity sensor.
2. The preparation method according to claim 1, characterized in that: The electrodes are interdigitated electrodes.
3. The preparation method according to claim 2, characterized in that: The precursor fiber is obtained by direct writing and depositing multiple layers back and forth in a direction perpendicular to the interdigital direction of the electrode through the electrospinning direct writing technology.
4. The preparation method according to claim 3, characterized in that: The precursor fiber is obtained by direct writing and depositing 100 layers back and forth in a direction perpendicular to the interdigital direction of the electrode through the electrospinning direct writing technology.
5. The preparation method according to claim 2, characterized in that: The electrode raw materials include but are not limited to single or multiple metals of Ag, Cu, Ni and Au; and / or, The electrode is designed to have 20 pairs of 40 fingers, each finger has a size of 100 μm×100 μm, and the gap between the fingers is 100 μm.
6. The preparation method according to claim 1, characterized in that: The particle-free ink has a silver acetate content of 1.4%, a zinc acetate content of 3.5%, a PEO content of 14%, a water-to-anhydrous ethanol volume ratio of 1:2, and a silver-to-zinc ratio of 1:2; and / or, The flexible substrate used is polyimide with a thickness of 1 mm; and / or, The electrospinning direct writing technology is to store ink in a syringe and deliver it to a needle through a precision injection pump, and the flexible substrate is driven by a motion platform to deposit nanofibers according to a pre-designed trajectory; and / or, The Zn / Ag / PEO nanowire is formed after being sintered at 50° C. for 60 minutes on a high-temperature sintering table; the Zn / Ag / PEO nanowire has a one-dimensional porous bionic nanostructure.
7. A flexible resistive humidity sensor based on Zn / Ag / PEO nanowire stack, characterized in that: The flexible resistive humidity sensor is manufactured by the preparation method according to any one of claims 1 to 6, comprising a flexible substrate, an electrode and a humidity sensitive material layer; the electrode is arranged on the top surface of the flexible substrate, the humidity sensitive material layer is arranged on the top surface of the electrode, and the electrode is led out by a wire; The humidity sensitive material layer is Zn / Ag / PEO nanowire.
8. The use of the flexible resistive humidity sensor according to claim 7, characterized in that: The flexible resistive humidity sensor is applied in the detection field, and the detection field includes but is not limited to food safety detection and industrial detection.
9. The use according to claim 8, characterized in that: The flexible resistive humidity sensor operates in a relative humidity range of 11% to 85% RH.
10. The use according to claim 8, characterized in that: The flexible resistive humidity sensor operates in a temperature range of 0°C to 120°C.
Citation Information
Cited By
Pressure sensor
CN120740818A
Flexible ultra-sensitive capacitive humidity sensor based on electrochemical interface barrier modulation and preparation method of flexible ultra-sensitive capacitive humidity sensor
CN121955121A